Cervical metastasis of undetermined origin: evaluation and criteria for management - Ayodele, Samuel O.; Ologe, Foluwasayo E. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Cervical metastatic cancer of undetermined primary site is described as the presence of metastasis in the cervical lymph node(s) without any identifiable primary site, despite detailed clinical and investigative evaluations. Identification of primary origin is still a big challenge even in the phase of modern diagnostic options. This review was meant to lay open the challenges and offer options of evaluation and managing these cases in a resource limited environment. Methods: The literature search was carried out to retrieve relevant published articles, books, guidelines. The search was limited to articles in English while unpublished literatures were excluded. Results: The process of metastasis might begin before the obvious growth of the primary mass, making detection of primary site of a malignant tumour difficult to determine. There is no current worldwide consensus for evaluation and treatment of cervical metastasis of undetermined primary; however, the primary purpose for management should be towards cure along with locoregional control. This is always based on a well-studied natural history of the mucosal squamous cell cancers of the upper aerodigestive tract. Conclusions: The first step in the work up remains thorough clinical evaluation and the minimum evaluation should include computed tomography scan of the head and neck, core needle biopsy of the metastatic cervical lymph node(s) for histological analysis, panendoscopy and biopsies from suspicious sites in the upper airway. Treatment modalities can be classified into modified radical neck dissection with or without adjuvant radiotherapy, radiotherapy alone, and combination of surgical intervention and chemoradiation.